If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24(24) = 12(12 + x) Multiply 24 * 24 576 = 12(12 + x) 576 = (12 * 12 + x * 12) 576 = (144 + 12x) Solving 576 = 144 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 576 + -12x = 144 + 12x + -12x Combine like terms: 12x + -12x = 0 576 + -12x = 144 + 0 576 + -12x = 144 Add '-576' to each side of the equation. 576 + -576 + -12x = 144 + -576 Combine like terms: 576 + -576 = 0 0 + -12x = 144 + -576 -12x = 144 + -576 Combine like terms: 144 + -576 = -432 -12x = -432 Divide each side by '-12'. x = 36 Simplifying x = 36
| 5/7*5/8 | | 7x^(1/2)=0 | | 6(1+3n)+2=44 | | 7x^(1/2) | | -3x-3=3x | | 14*11=84 | | 5x-4*5=3x-2 | | 6x+4-13x=-24 | | -34=v+42-50 | | 13+7q=15+16q | | 25=5(8x+5)+2x | | 5x-1*2=7 | | a*3+7=14 | | x^2-90x+225=0 | | x^2+28x-104=0 | | 11q+8q=16+7q | | (4x+9)(x-6)=0 | | X+2=5(x-2) | | 8(5v+3)=-56 | | y=2x^3-24x-2 | | x*8=2.25 | | (x-8)(x-1.67)=0 | | 7-3/m18/m | | -60=-6(4b+2) | | 6(-9+7x)=-306 | | -2(8+x)=-12 | | -2(8+n)=-10 | | (3x-6)+2(2x-5)=26 | | 64+64+x+x=180 | | 5(m+9)-8(12-m)= | | 3(7x+7)=189 | | 8x-16=9x+8 |